Kinetics of the a-C3H5 + O2 reaction, investigated by photoionization using synchrotron radiation. Issue 16 (17th January 2018) - Schleier, D.; Constantinidis, P.; Faßheber, N.; Fischer, I.; Friedrichs, G.; Hemberger, P.; Reusch, E.; Sztáray, B.; Voronova, K.
Abstract : The kinetics of the allyl + O2 reaction has been studied in a flow tube reactor, using VUV synchrotron radiation for product detection. Abstract : The kinetics of the combustion-relevant reaction of the allyl radical, a-C3 H5, with molecular oxygen has been studied in a flow tube reactor at the vacuum ultraviolet (VUV) beamline of the Swiss Light Source storage ring, using the CRF-PEPICO (Combustion Reactions Followed by Photoelectron Photoion Coincidence Spectroscopy) setup. The ability to measure threshold photoelectron spectra enables a background-free detection of reactive species as well as an isomer-specific analysis of reaction products. Allyl was generated by direct photodissociation of allyl iodide at 266 nm and 213 nm and indirectly by the reaction of propene with Cl atoms, which were generated by photolysis from oxalyl chloride at 266 nm. Experiments were conducted at room temperature at low pressures between 0.8 and 3 mbar using Ar as the buffer gas and with excess O2 to maintain nearly pseudo-first-order reaction conditions. Whereas allyl was detected by photoionisation using synchrotron radiation, the main reaction product allyl peroxy was not observed due to dissociative ionisation of this weakly bound species. From the concentration–time profiles of the allyl signal, second-order rate constants between 1.35 × 10 11 cm 3 mol −1 s −1 at 0.8 mbar and 1.75 × 10 11 cm 3 mol −1 s −1 at 3 mbar were determined. The rates obtained for the different allyl radical generation schemes agree well with each other, but are about a factor of 2 higher than the ones reported previously using He as a buffer gas. The discrepancy is partly attributed to the higher collision efficiency of Ar causing a varying fall-off behavior. When allyl is produced by the reaction of propene with Cl atom, an unexpected product is observed at m / z = 68, which was identified as 1, 3-butadienal in the threshold photoelectron spectrum. It is formed in a secondary reaction of allyl with the OCCl radical, which is generated in the 266 nm photolysis of oxalyl chloride.